The heterogeneity of lung involvement in vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic syndrome: a case of hypersensitivity pneumonitis-like pattern - C. Iannone; M.R. Pellico; C. Campochiaro; L. Tescaro; M. Zompatori; A. Caminati; S. Harari; R. Caporali (PAGEPress Publications, 2024)
Vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic (VEXAS) syndrome is a recently characterized disease associated with somatic mutations in the UBA1 gene, which cause dysregulation of ubiquitin-mediated processes. This case describes a 71-year-old male patient with VEXAS syndrome who presented with refractory lung inflammation with a pattern similar to computed tomography hypersensitivity pneumonitis, a novel finding in VEXAS syndrome. The presented clinical case highlights the protean involvement of the lung in VEXAS syndrome and emphasizes the importance of considering interstitial lung disease in the differential diagnosis.